2002
DOI: 10.1007/bf02703771
|View full text |Cite
|
Sign up to set email alerts
|

Murine model of BCG lung infection: Dynamics of lymphocyte subpopulations in lung interstitium and tracheal lymph nodes

Abstract: C57Bl/6 female mice were infected with an intrapulmonary dose of 2.5 x 10(4) BCG (Mycobacterium bovis Bacillus Calmette-Guerin). Lymphocyte populations in lung interstitium and lung-associated tracheal lymph nodes (LN) were examined at 1, 2, 4, 5, 6, 8 and 12 weeks after infection. BCG load in lungs peaked between 4-6 weeks post-infection and declined to very low levels by the 12th week of infection. Lung leukocytes were obtained over the course of infection by enzyme digestion of lung tissue followed by centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…To determine whether Treg are present in the lung and whether they accumulate during mycobacterial lung infection, we measured the number of CD4 + CD25 + Foxp3 + Treg in the lung after an intranasal challenge with BCG. BCG is attenuated M. bovis that causes a pulmonary infection in mice similar to that of virulent mycobacteria as it results in the infiltration of lymphocytes, macrophages and granulocytes to the lung, 21 and IFN‐γ production is required for control of the infection 22 . We found that over the first 14 days of BCG infection the total number of Treg in the lung almost trebled in control mice treated with rat IgG (Figure 1A), indicating that this cell subset is indeed present in the normal lung (day 0) and increases significantly during a mycobacterial lung infection.…”
Section: Resultsmentioning
confidence: 99%
“…To determine whether Treg are present in the lung and whether they accumulate during mycobacterial lung infection, we measured the number of CD4 + CD25 + Foxp3 + Treg in the lung after an intranasal challenge with BCG. BCG is attenuated M. bovis that causes a pulmonary infection in mice similar to that of virulent mycobacteria as it results in the infiltration of lymphocytes, macrophages and granulocytes to the lung, 21 and IFN‐γ production is required for control of the infection 22 . We found that over the first 14 days of BCG infection the total number of Treg in the lung almost trebled in control mice treated with rat IgG (Figure 1A), indicating that this cell subset is indeed present in the normal lung (day 0) and increases significantly during a mycobacterial lung infection.…”
Section: Resultsmentioning
confidence: 99%
“…The role of NK cells in the innate response to Mtb is evidenced by their increased number and activated status in the lungs of infected mice (Saxena et al, 2002;Feng et al, 2006) and their innate effector function is illustrated by their capacity to lyse Mtbinfected human monocytes (Vankayalapati et al, 2005). This capacity is due to their intracellular preformed perforin and granulysin granules, which can also directly kill extracellular mycobacteria and restrict mycobacterial growth in an apoptosis-dependent but Fas/Fas ligand (FasL) independent manner (Stenger et al, 1998;Brill et al, 2001;Millman et al, 2008).…”
Section: Nk Cells and Gd T Cellsmentioning
confidence: 98%
“…Cell suspensions were prepared from lungs or solid tumors by digestion with a mixture of collagenase, hyaluronidase, elastase, and DNase (37,38), purified by density gradient centrifugation (39), washed, and reconstituted in 2 mg/ml mouse IgG in BSA-PBS. Samples were stained as described below, and analyzed by flow cytometry, following procedures used previously to examine B cells from CLL patients (21,25).…”
Section: Analysis Of Tumor Cellsmentioning
confidence: 99%